From Lab to Field: Damp Heat Testing and its Implications for PV Module Service Lifetime - Abdulkerim Gok (Global Challenges)
Abstract Damp heat testing, as outlined in the IEC 61215 standard, evaluates PV modules under prolonged humidity exposure. However, its effectiveness as a reliability test remains debated. This study maps damp heat testing times equivalent to a service lifetime of 30 years across Europe, highlighting the impact of local climate conditions. The activation energy of power degradation is key in determining testing times. For an activation energy of 0.6 eV, testing times range from over 2250 h in southern Europe to <750 h in northern Europe. In central Europe, testing times generally range from 1250 to 1750 h. Madrid and Rome stand out among major European capitals for their testing times, with Madrid having one of the shortest and Rome one of the longest. In Madrid, increasing the activation energy from 0.4 to 0.8 eV reduces the testing time from 5548 h to just 290 h. To ensure the standard testing time of 1000 h represents a service lifetime of 30 years across Europe, the activation energy should be at least 0.7 eV. These findings emphasize the need for customized testing protocols that consider regional climate differences and design factors, rather than relying on a one‐size‐fits‐all approach.